QUALITY TESTING OF HEAT TREATMENT OF MEDIUM-CARBON STEEL CONSTRUCTION ITEMS BASED ON THE BIPOLAR PULSED REMAGNETIZATION - V. F. Matyuk; V. A. Burak (Приборы и методы измерений, 2015)
The features of bipolar pulsed remagnetization of construction medium-carbon steel items for testing the heat treatment temperature and structure of these items are discussed, the methods of bipolar pulse remagnetization providing testing of items of considered steels are suggested.